General classification the axonometric projection of the graphics image - Фесенко, М. Б. (Problems of Informatization and Control, 2005)
The concept of axonometry witch scientifically grounded inclusion of orthographic projections and central perspective is determinated. On that base is accomlished an classification the axonometric projections of graphic objects, which allows to detect an intercommunication between separated projections, that are used in various systems, where computer graphics is applicafed